The relationship between pregnant women’s knowledge and participation in HIV testing at Nisam Health Center - Elly Nizar; Fitriani Fitriani; Myrna Lestari AB; Elvieta Elvieta; Aida Fitriani (Journal of Midwifery and Nursing, 2026)
This research aimed to examine the association between pregnant women’s knowledge and their involvement in HIV testing at the Nisam Health Center, North Aceh Regency. The study was motivated by the relatively low level of participation among pregnant women in HIV screening, which is crucial for early identification and prevention of mother-to-child HIV transmission. A quantitative analytic method with a cross-sectional design was applied. The study population included all pregnant women attending antenatal care (ANC) services at the Nisam Health Center, and 60 participants were chosen through purposive sampling. Data were obtained using structured questionnaires and analyzed with the Chi-Square statistical test. The findings indicated that more than half of the respondents (31 women or 53.4%) demonstrated a moderate level of knowledge, while most participants (44 women or 75.8%) had undergone HIV testing. The statistical results showed a significant correlation between the respondents’ knowledge level and their participation in HIV testing (p = 0.001 < 0.05). Therefore, it can be inferred that higher knowledge among pregnant women increases the likelihood of their engagement in HIV screening. Health professionals are encouraged to strengthen educational efforts and counseling to enhance awareness of the importance of HIV testing during pregnancy as a preventive measure against vertical transmission.